Výroba raznice do kůže s využitím 3D tisku - Vrána, Pavel (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2023)
Práce se zaměřuje na možnosti využití technologie 3D tisku pro výrobu raznic do kůže a popisem vlivů ovlivňující proces ražení, jako je například množství obsažené vody, tvrdost jednotlivých oblastí usně nebo vliv tloušťky kůže. Pro popis chování kůže a raznice při procesu ražení na hydraulickém lise byl navržen experiment, pomocí kterého se určily regresivní křivky popisující oblast pěchování kůže a oblast vybočení raznice. Jednotlivé křivky raznic vyrobené z materiálů určené pro FDM a DLP tisk byly srovnány s konvenčně vyráběnou mosaznou raznicí. Porovnáním křivek se určila vhodnost materiálu pro ražbu. Materiály PLA a Resin - Basic dosahují požadovaných parametrů a je možné je použít. Využití technologie 3D tisku otvírá možnosti výroby jak rozměrných, tak velmi detailních raznic, při výrazném snížení ceny produktu.

The thesis focuses on the possibilities of using 3D printing technology for the production of leather stamps and describes the influences affecting the stamping process, such as the amount of water contained, the hardness of individual areas of the leather or the effect of the thickness of the leather. In order to describe the behaviour of the leather and the stamp during the embossing process on a hydraulic press, an experiment was designed to determine regression curves describing the skin deformation area and the stamp buckling area. The individual curves of stamps made from materials designed for FDM and DLP printing were compared with conventionally manufactured brass stamps. By comparing the curves, the suitability of the material for embossing was determined. PLA and Resin - Basic materials achieve the required parameters and can be used. The use of 3D printing technology opens up the possibility of producing both large and highly detailed stampings, at a significant reduction in product cost.
Production of a stamp for leather using 3D printing
Keywords: 3D tisk; výroba raznic; kůže; FDM; DLP; 3D printing; production of stamps; leather; FDM; DLP